The Relationship Between Convective Clustering and Mean Tropical Climate in Aquaplanet Simulations. (8th August 2020) - Popp, Max; Lutsko, Nicholas J.; Bony, Sandrine
Abstract: Convective clustering, the spatial organization of tropical deep convection, can manifest itself in two ways: through a decrease in the total area covered by convection and/or through a decrease in the number of convective areas. Much of our current understanding of convective clustering comes from simulations in idealized radiative convective equilibrium (RCE) configurations. In these simulations the two forms of convective clustering tend to covary, and their individual effects on the climate are thus hard to disentangle. This study shows that in aquaplanet simulations with more realistic boundary conditions, such as meridional gradients of surface temperature and rotational forces, the two aspects of convective clustering are not equivalent and are associated with different impacts on the large‐scale climate. For instance, reducing the convective area in the equatorial region in the aquaplanet simulations results in broader meridional humidity and rain distributions and in lower tropospheric temperatures throughout the tropics. By contrast, the number of convective regions primarily impacts the zonal variance of humidity‐related quantities in the aquaplanet simulations, as the distribution of convective regions affects the size of the subsidence regions and thereby the moistening influence of convective regions. The aquaplanet simulations confirm many other qualitative results from RCE simulations, such as a reduction of equatorial tropospheric humidity when the area covered by convection diminishes. Plain Language Summary: Strong precipitation events in Earth's tropics are associated with regions of strong upward motions that can extend over the entire depth of the troposphere. These regions of strong upward motions are not uniformly distributed throughout the tropics but occur mostly as clusters of various shapes and sizes, typically within a narrow zonal band. We show here with idealized climate simulations that different forms of spatial organization of the regions of upward motions have distinct impacts on the climate, highlighting the need to consider several metrics to characterize the organization. For instance, reducing the area covered by upward motions close to the equator results in broader meridional humidity and rain distributions. By contrast, the number of regions of upward motion primarily impacts the zonal variance of humidity‐related quantities. Key Points: The impact of convective clustering on tropical climate depends on both the total convecting area and on the number of convective clusters The total convective area affects the meridional distribution of water; the number of convective regions affects the zonal variance of water Many findings from radiative convective equilibrium studies are confirmed in aquaplanet simulations with realistic sea surface temperatures